Breast Lymphoma: Multimodality Case-Based Imaging Review - Gillis , E.; Lamb , L; Lehman , C. (Seram, 2021)
Background Information: Breast lymphoma, both primary (PBL) and secondary (SBL), are relatively uncommon, accounting for less than 1% of all breast malignancies.1,2 The clinical presentations and imaging features can be indistinguishable from primary breast carcinoma. Similarly, breast implant-associated anaplastic large cell lymphoma (BIAALCL) is a rare disease with non-specific imaging features and has recently captured the attention of the public and medical community.3 Accurate and timely diagnosis of all three types of breast lymphoma require awareness of these diseases and recognition of the possibility of their presence based on clinical history and imaging presentation. Educational Goals/Teaching Points: In this exhibit, we summarize epidemiological studies to provide radiologists with knowledge of population sub-types in which the diagnosis of lymphoma should be considered. We describe common clinical presentations of PBL, SBL, and BIAALCL to clarify the clinical history that can prompt consideration of lymphoma in a differential diagnosis. We present cases with classic imaging features to provide familiarity with these rare entities. We review pathology requirements at the time of biopsy when lymphoma is in the differential diagnosis, including proper handling of specimens and laboratory testing requests. Key Anatomic/Physiologic Issues and Imaging Findings/Techniques: PBL is almost always non-Hodgkin lymphoma, most commonly diffuse large B-cell lymphoma. PBL typically presents as a palpable mass. SBL is the most common metastasis to the breast and often presents with “B symptoms” (fever, weight loss, night sweats) as the disease is usually advanced elsewhere. Imaging features of PBL and SBL include: isodense to hyperdense oval mass(es) at mammography; hypoechoic or mixed-echogenicity hypervascular mass at ultrasound; enhancing mass with type II kinetics at magnetic resonance imaging; and high fluorine 18–fluorodeoxyglucose avidity at positron emission tomography.1 BIAALCL should be considered in seromas detected greater than one year after implant placement, although the average time from placement to presentation is typically eight to ten years.4 BIAALCL typically presents with an effusion/seroma and/or mass. Radiologists performing biopsy of suspected breast lymphoma should alert the pathologist to the diagnostic possibility so appropriate immunohistochemical staining can be performed. Institutional guidelines for appropriate preservative agents (buffered formalin, Roswell Park Memorial Institute (RPMI) medium, and or saline) should be confirmed between pathology and radiology. Conclusion: Breast lymphoma is a rare disease and the diagnosis can be particularly challenging given its non-specific imaging features and clinical presentation. Familiarity with the epidemiology of breast lymphoma, its imaging appearance, and requirements for diagnosis can empower the radiologist to appropriately consider it in a differential diagnosis and assist in accurate and timely diagnosis through proper coordination with pathologists at their institutions.